1983
DOI: 10.1161/01.cir.68.3.490
|View full text |Cite
|
Sign up to set email alerts
|

False suspicion of coronary heart disease: a 7 year follow-up study of 36 apparently healthy middle-aged men.

Abstract: Latent coronary heart disease was suspected in 115 of 2014 apparently healthy middleaged men after a baseline cardiovascular survey. One hundred five of these men underwent angiography and 36 were found to have normal coronary arteries (group 1). A 7 year follow-up survey revealed that: (1) three had died of sudden cardiac death, (2) four had received a diagnosis of cardiomyopathy, (3) one had developed aortic dilatation/aortic regurgitation since the baseline survey, (4) they all had a significantly more rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…22 The clinical significance of a positive exercise test in asymptomatic subjects is controversial because it may occur in the absence of coronary artery disease on angiography. 1523 However, some patients with a positive exercise test but normal coronary arteriograms subsequently develop clinical heart disease, 24 and many have mild cardiac dysfunction suggestive of cardiomyopathy. 24 ' 25 It is possible, therefore, that the increased incidence of a positive exercise test in diabetic patients is partly related to a subclinical cardiomyopathy.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…22 The clinical significance of a positive exercise test in asymptomatic subjects is controversial because it may occur in the absence of coronary artery disease on angiography. 1523 However, some patients with a positive exercise test but normal coronary arteriograms subsequently develop clinical heart disease, 24 and many have mild cardiac dysfunction suggestive of cardiomyopathy. 24 ' 25 It is possible, therefore, that the increased incidence of a positive exercise test in diabetic patients is partly related to a subclinical cardiomyopathy.…”
Section: 12mentioning
confidence: 99%
“…1523 However, some patients with a positive exercise test but normal coronary arteriograms subsequently develop clinical heart disease, 24 and many have mild cardiac dysfunction suggestive of cardiomyopathy. 24 ' 25 It is possible, therefore, that the increased incidence of a positive exercise test in diabetic patients is partly related to a subclinical cardiomyopathy. 26 ' 27 Although abnormal myocardial metabolism in diabetes might also give rise to an increased frequency of false-positive exercise tests, our follow-up data indicate that the risk of developing coronary heart disease is at least as great in diabetic patients with a positive test as it is in nondiabetic subjects, and it seems unlikely, therefore, that a false-positive test is more common in diabetic patients.…”
Section: 12mentioning
confidence: 99%
“…This is curious given that the bulk of available data within the literature supports medical therapy over early intervention in the majority of stable patients (18). However, there are a number of plausible explanations for this: First, the negative (and positive) predictive value of investigations including the exercise treadmill test, stress echocardiogram and nuclear scintigraphy are far from ideal and can result in diagnostic uncertainty, particularly as each provides physiological rather than anatomical data (19)(20)(21); Second, increasing pressure on rapid patient throughput in the healthcare system has led to a 'one-stop' clinic approach, where a definitive management plan is formulated at the initial clinic visit; third, there has been a progressive shift in many healthcare systems (including ours) towards a more 'defensive' style of medical practice with anatomical-imaging often being considered essential for diagnostic certainty (22). Interestingly, the approach of direct referral for angiography without preprocedural non-invasive assessment (at least in those with typical angina and high pretest probability (> 67%) for coronary disease) is advocated by some current guidelines for management of stable angina pectoris (1).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of asymptomatic patients with an abnormal exercise test, who have no risk factors, will not have coronary disease, according to Bayes' Theorem; however, in some of the published studies [6,8] this has not turned out to be the case. These contradictions man date careful interpretation of exercise testing results in this population.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological data from the Seat tle Heart Watch study of Bruce et al [7] indicate testing those with risk factors is most productive. Erikssen et al [8] did angiographies on 105 asymptomatic patients, because during a screening test they were found to have exercise-induced ST depression. These authors found abnormal coronary arteries in 69 patients with a predic tive value of 69 %.…”
Section: Introductionmentioning
confidence: 99%